(untitled) (World Bulletin of Social Sciences, 2024)
Project-Based Learning (PBL) holds immense potential in higher education, yet its implementation presents distinct challenges. This article delves into the complexities of integrating PBL into university courses, exploring both the hurdles and the promising opportunities it offers. Drawing on existing research and theoretical frameworks, the article examines key challenges such as faculty development, time constraints, curriculum alignment, and assessment strategies. It further highlights best practices like authentic project design, scaffolding, and technology integration, providing practical guidance for overcoming the identified challenges. By exploring successful implementation strategies and theoretical underpinnings like constructivism and the ADDIE model, the article aims to empower educators and institutions to embrace PBL’s transformative potential. Ultimately, it argues that effective PBL implementation can equip students with the critical thinking, problemsolving, and collaboration skills necessary to thrive in a rapidly evolving world